THE USE OF DISCOURSE MARKERS AS AN INTERACTIVE FEATURE IN SCIENCE LECTURE DISCOURSE IN L2 SETTING - Akhyar Rido (TEFLIN, 2010)
Abstract: The objective of this research is to investigate the function of discourse markers as an interpersonal-interactive feature in a science lecture in second language (L2) setting in Malaysia. This research employs qualitative method while the data are gathered through non-participant observation and video-recording. From the findings, there are various discourse markers found. Macro markers signal the transition of the moves and indicate a shift of one topic/sub-topic to another topic/sub-topic. Meanwhile, micro markers signal the internal or ideational relations within sentences. In conclusion, the use of discourse markers will help students to comprehend a lecture.